Effect of the dangling aromatic ring on neutral luminescent bis(phosphine) Cu(i)/Ag(i) complexes with the asymmetric pyridyl-tetrazolate ligands. Issue 42 (26th September 2022) - Xiang, Jing; Wang, Li-Xin; Zhang, Xu; Zhu, De-Sheng; Wang, Lei; Liu, Lu-Lu; Leung, Chi-Fai; Xiang, Jing
Abstract : The Cu(i ) complex of a pyridyl-tetrazolate ligand exhibits enhanced luminescence, which was fabricated as an OLED device with an EQE of 7.7%. Abstract : A series of neutral luminescent bis(phosphine) Cu(i ) complexes of pyridyl-tetrazolate ligands (L 1 –L 3 ) with the general formula [Cu I (L n )(P^P)] (1–6 ) were synthesized, which have been well characterized by IR, UV/vis, CV, 1 H NMR and 31 P NMR. For comparison, an Ag(i ) complex [Ag I (L 2 )(PPh3 )2 ] (7 ) was also synthesized. The crystal structures of 2 and 7 have been further determined by X-ray crystallography. All these Cu(i ) compounds show bright luminescence in the solid state with photoluminescence quantum yields (PLQYs) in the range of 25.8% to 85.0%. More interestingly, the Cu(i ) complexes bearing an additional dangling aromatic ring on the diimine ligands exhibit enhanced luminescent performance in various solutions and their PLQYs are significantly higher than those of related Cu(i ) complexes without steric protection. Compared with 1, the Cu(i ) complexes with an additional dangling tetrazole moiety show a significant solvatochromic effect, which is uncommon for luminescent Cu(i ) complexes. Moreover, [Cu I (L 2 )(PPh3 )2 ] (2 ) was further designed as an OLED material, which showed a high external quantum efficiency of 7.7%.